Efficiency in the Iranian Tax System Price Elasticity & Tax Lag Concerns - abbas shakeri; Mir Hossein Mousavi (فصلنامه پژوهش‌های اقتصادی ایران, 2004)
Tax income is the most important source of income for government after the oil income in Iran. The tax system, however, suffers from two factors: long lags, and inflexibility. In this paper, we investigate the efficiency in the Iranian tax system with respect to the two factors above using cointegration analysis for period 1982:3-2002:4. The results indicate that in the long run there is a twenty-two-month lag in tax collection, and, 9-18 month lag in short term. Since the tax system is not flexible enough in response to price changes, this time lag in tax collection along with inflation has led to a decline in real income tax.